Quantitative comparison of 3D third harmonic generation and fluorescence microscopy images. Issue 1 (2nd May 2017) - Zhang, Zhiqing; Kuzmin, Nikolay V.; Groot, Marie Louise; de Munck, Jan C.
Abstract: Third harmonic generation (THG) microscopy is a label‐free imaging technique that shows great potential for rapid pathology of brain tissue during brain tumor surgery. However, the interpretation of THG brain images should be quantitatively linked to images of more standard imaging techniques, which so far has been done qualitatively only. We establish here such a quantitative link between THG images of mouse brain tissue and all‐nuclei‐highlighted fluorescence images, acquired simultaneously from the same tissue area. For quantitative comparison of a substantial pair of images, we present here a segmentation workflow that is applicable for both THG and fluorescence images, with a precision of 91.3 % and 95.8 % achieved respectively. We find that the correspondence between the main features of the two imaging modalities amounts to 88.9 %, providing quantitative evidence of the interpretation of dark holes as brain cells. Moreover, 80 % bright objects in THG images overlap with nuclei highlighted in the fluorescence images, and they are 2 times smaller than the dark holes, showing that cells of different morphologies can be recognized in THG images. We expect that the described quantitative comparison is applicable to other types of brain tissue and with more specific staining experiments for cell type identification. Abstract : Third harmonic generation (THG) microscopy is a label‐free imaging technique that shows great potential for rapid pathology of brain tissue during brain tumor surgery. However, the interpretation of THG brain images should be quantitatively linked to images of more standard imaging techniques. Such a quantitative link between THG images of mouse brain tissue and all‐nuclei‐highlighted fluorescence images is established here, acquired simultaneously from the same tissue area. The presented segmentation workflow is applicable for both THG and fluorescence images. The described quantitative comparison might be applicable to other types of brain tissue and with more specific staining experiments for cell type identification.